Anemia as a potent marker of in-hospital mortality in patients admitted to the cardiac intensive care unit: Data from the Critical Care Cardiology Trials Network (CCCTN) Registry - Christine Chow; Rasheed Durowoju; Carlos Alviar; Gregory W Barsness; Howard A Cooper; Lori B Daniels; Xuan Ding; Shahab Ghafghazi; Umesh Gidwani; Michael Goldfarb; Dustin Hillerson; Jason N Katz; et al. (Journal of Intensive Medicine)
Background: Anemia is common in critically ill patients and is associated with poor outcomes. We investigated the prevalence of anemia and its association with in-hospital outcomes among patients admitted to cardiac intensive care units (CICUs) and subgroups within this population. Methods: The Critical Care Cardiology Trials Network (CCCTN) is a multicenter network of tertiary CICUs in North America. CICU admissions with available baseline hemoglobin (Hgb) between 2017 and 2023 were included in this analysis. Patients were stratified by Hgb levels (Hgb <8 g/dL, 8 g/dL ≤ Hgb <10 g/dL, 10 g/dL ≤ Hgb <12 g/dL, 12 g/dL ≤ Hgb <14 g/dL, and ≥14 g/dL). The ≥14 g/dL group was used for reference. The association of Hgb level and in-hospital mortality was examined by multivariable logistic regression. Results: Among 28,585 patient admissions (median age 67 years, 36.7 % female), the median Hgb was 12.1 g/dL (interquartile range: 10.1–13.9), with 48.3 % of patients who meet criteria for anemia (Hgb <12 g/dL). The adjusted relative odds of in-hospital mortality was highest for patients with Hgb <8 g/dL (1.60, 95 % confidence interval [CI]: 1.35 to 1.89, P < 0.0001), followed by patients with 8 g/dL≤ Hgb <10 g/dL (adjusted relative odds =1.51, 95 % CI: 1.32 to 1.73, P < 0.0001), and patients with Hgb 10 g/dL≤ Hgb<12 g/dL (adjusted relative odds=1.24, 95 % CI: 1.09 to 1.41, P=0.0012). This association was present among those with non-acute coronary syndrome (ACS) cardiogenic shock (n=4255) and those with non-cardiogenic shock ACS (n=7194). Conclusions: Anemia was present in nearly half of patients admitted to CICUs. Lower admission Hgb is independently associated with higher in-hospital mortality in a graded relationship among patients with cardiac critical illness.